(untitled) (Revista Latino-Americana de Enfermagem, 2005)
This study aimed at 1) identifying social, demographic and clinical characteristics of mentally-ill patients and their relatives and 2) analyzing their conceptions concerning mental illness and psychiatric care. The Attitude Measurement Scale (AMS) was used. Quantitative and qualitative analyses of the data were carried out. The 104 study subjects comprised 35 patients and 69 relatives (n=104). The Mann-Whitney Test was used for comparing the opinions of patients X relatives and the Wilcoxon Test for comparing Concept and Care. There was homogeneity in the distribution of the subjects' scores for both Concept and Care. No questions stood out or were concentrated in either group. The subjects' profile shows the transition from asylum care to innovative experiences, although there is still a concentration of drug treatments and dependence on the psychiatric institution.